2017
DOI: 10.1124/mol.116.106880
|View full text |Cite
|
Sign up to set email alerts
|

The (α4)3(β2)2Stoichiometry of the Nicotinic Acetylcholine Receptor Predominates in the Rat Motor Cortex

Abstract: The 42 nicotinic acetylcholine receptor (nAChR) is important in central nervous system physiology and in mediating several of the pharmacological effects of nicotine on cognition, attention, and affective states. It is also the likely receptor that mediates nicotine addiction. This receptor assembles in two distinct stoichiometries: (4)(2) and (4)(2), which are referred to as high-sensitivity (HS) and low-sensitivity (LS) nAChRs, respectively, based on a difference in the potency of acetylcholine to activate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…This conformational heterogeneity in β2 subunit structure likely further adds to the instability of the β-β interface. These structural observations suggest that the 3α:2β stoichiometry would be the predominant assembly in the absence of other factors, consistent with observations in rat motor cortex 11 and in recombinant mammalian expression 9 . In our sample preparation, we exploited nicotine and low temperature during viral transduction to boost overall receptor expression, two factors that are known to shift the stoichiometry toward the 2α:3β assembly 9 .…”
supporting
confidence: 88%
“…This conformational heterogeneity in β2 subunit structure likely further adds to the instability of the β-β interface. These structural observations suggest that the 3α:2β stoichiometry would be the predominant assembly in the absence of other factors, consistent with observations in rat motor cortex 11 and in recombinant mammalian expression 9 . In our sample preparation, we exploited nicotine and low temperature during viral transduction to boost overall receptor expression, two factors that are known to shift the stoichiometry toward the 2α:3β assembly 9 .…”
supporting
confidence: 88%
“…In support, W176 from the principal face of the 2 subunit contacts H142 from the complementary face the 4 subunit [49], and together the two residues could contribute to an interfacial drug binding site. In addition, NS9283 did not compete against [ 3 H]-cytisine binding to rat cortical tissue [55], a region rich in (4)3(2)2 receptors [40], suggesting it does not bind to the orthosteric sites. Nevertheless, the 2-4 subunit interfaces might not be the binding sites for NS9283, but may instead serve as transduction elements for potentiation.…”
Section: Discussion-mentioning
confidence: 95%
“…Seminal studies showed that when 4 and 2 subunits were co-expressed, the agonist dose-response relationship, based on recordings of voltage clamped macroscopic current, exhibited high and low sensitivity components [12,13,15,40]. The high sensitivity component was shown to arise from receptors with two 4 and three 2 subunits, whereas the low sensitivity component was shown to arise from receptors with three 4 and two 2 subunits [13,17].…”
Section: Discussion-mentioning
confidence: 99%
“…The α4β2 nAChR is a pentameric protein that exhibits two different stoichiometries: a high-ACh sensitivity conformation (HS), (α4) 2 (β2) 3 , and a low-ACh sensitivity conformation (LS), (α4) 3 (β2) 2 (26, 27). To determine experimentally whether the identified AA replacements provide resistance to epibatidine, we used site-directed mutagenesis to introduce poison frog AA replacements into human nAChRs.…”
Section: Electrophysiology Of Aa Replacements In the Poison Frog Nachrmentioning
confidence: 99%